A study on different factors influencing on empowering employees: Evidence from food industry - Masod Pourkiani; Ali Naderifar (Management Science Letters)
This paper studies the effects of different factors on empowering employees in one of Iranian food makers named Razavi Foods Products Co. The study designs a questionnaire in Likert scale and distributes it among 83 out of 105 employees who work for this food producer. Cronbach alpha is equal to 0.91, which is well above the minimum acceptance level. In addition, Kolmogorov–Smirnov test has indicated that all data were normally distributed. The results of Pearson correlation test has indicated that work place was the most influential factor affecting positively on empowering employees followed by having crystal clear objectives on responsibilities and employees’ authorities. In addition, the implementation of stepwise regression technique has indicated that work process was the most important factor followed by process optimization and having clear objectives.